The inhibition of amine oxidase and the central stimulating action of the stereoisomeric amphetamines and 1-phenylethylamines - Grana, E. (1959)
The stereoisomers of amphetamine and 1-phenylethylamine have been studied in the rat both as central stimulants and as inhibitors of amine oxidase from brain, liver, and kidney. There was no correlation between these two effects; thus it is unlikely that the central stimulating action of amphetamine is due to inhibition of amine oxidase.